2013
DOI: 10.1117/1.jbo.18.4.040503
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional deconvolution microfluidic microscopy using a tilted channel

Abstract: Abstract. We have developed a microfluidic device that enables the computation of three-dimensional (3-D) images of flowing samples. Using a microfluidic channel that is tilted along the optical axis, we record several progressively defocused images of the flowing sample as it passes across the focal plane. The resulting focal stack is then deconvolved to generate 3-D images. Experimental results on flowing yeast cells reveal both volume and surface profile information. The microfluidic channel eliminates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Here, we introduced a method for quantitative analysis and 3D imaging, which use deconvolution algorithms, rapidly and precisely reconstructing 3D objects, allowing a better visual understanding of the image data and a more accurate quantitative assessment of the 3D object (Pegard and Fleischer, 2013;Chakrova et al, 2016). Compared with the control group, the HCD feeding significantly induced the hepatic ROS levels increase, which was inhibited by BBR (5 mM).…”
Section: Quantification Analysis Of Hepatic Ros Level Based On 3d Modmentioning
confidence: 99%
“…Here, we introduced a method for quantitative analysis and 3D imaging, which use deconvolution algorithms, rapidly and precisely reconstructing 3D objects, allowing a better visual understanding of the image data and a more accurate quantitative assessment of the 3D object (Pegard and Fleischer, 2013;Chakrova et al, 2016). Compared with the control group, the HCD feeding significantly induced the hepatic ROS levels increase, which was inhibited by BBR (5 mM).…”
Section: Quantification Analysis Of Hepatic Ros Level Based On 3d Modmentioning
confidence: 99%
“…These imaging systems are, in general, referred to as Imaging Flow Cytometry (IFC) systems. [18][19][20][21][22][23][24][25] While IFC systems offer the advantages of both microscopy (acquisition of morphological features from images and high spatial resolution) and flow cytometry (automation, high sensitivity, and high-throughput), 26 one of the major limitation is the requirement of using high speed cameras. Most of the reported IFC systems in the literature employed cameras with frame rates of few to several thousand frames per second.…”
Section: Introductionmentioning
confidence: 99%
“…Ethan et al, have demonstrated the use of micro-optics and microfluidics to simultaneously image multiple field-of-views, in order to achieve a high-throughput of about 20,000 beads per second (Gorthi et al, 2011). Microfluidic IFC has also been extended to capture 3D morphology of cells (Gorthi & Schonbrun, 2012;Fleischer & Pgard 2013;Wu et al, 2013;Sung et al, 2014). In microfluidics-based IFC, the cells in suspension are allowed to flow across the microfluidics channel and the video of the flow stream is captured using a high-speed microscopy system.…”
Section: Introductionmentioning
confidence: 99%